The influence of substrate surface energy on the adhesion compatibility of epoxy adhesive using molecular simulation tool - Nizam, N.F.I.A. (Asian Research Publishing Network, 2018)
The utilization of structural adhesive onto aluminium oxide (Al2O3), aluminium (Al) and polyvinyl chloride (PVC) can be remarkably observed in much industrial application such as aerospace, automotive, electronics and medical. Due to the abundant prominent properties exhibited by epoxy resin, the relevancy of opting for it as adhesive agent in the aforementioned industry is believed to be highly beneficial. However, the feasibility of implementing the idea is still not clear. It was the objective of this study to shed light on those aspects which are lacking in literature. In this study, Materials Studio 6.0 will be utilized to model and simulate the compatibility and adhesion strength of epoxy resin with three different substrates i.e. Al2O3, Al and PVC. Simulation consist of molecular dynamics (MD) and molecular mechanics (MM) reveal the significant influence that each substrate gives in promoting the adhesion compatibility within the epoxy-substrate system. The computed result has shown significant agreement upon the experimental data in which the epoxy resin is most compatible with Al2O3, followed by Al and lastly with PVC. Â© 2006-2018 Asian Research Publishing Network (ARPN).